Relationships between the concentration of particulate organic nitrogen and the inherent optical properties of seawater in oceanic surface waters - A. Fumenia; H. Loisel; R. A. Reynolds; D. Stramski (Biogeosciences)
The concentration of particulate organic nitrogen (PON) in seawater plays a central role in ocean biogeochemistry. The limited availability of PON data obtained directly from in situ sampling methods hinders development of a thorough understanding and characterization of spatiotemporal variability in PON and associated source and sink processes within the global ocean. Measurements of inherent optical properties (IOPs) of seawater, which can be performed over extended temporal and spatial scales from various in situ and remote-sensing platforms, represent a valuable approach to address this gap. We present the analysis of relationships between PON and particulate IOPs, including the absorption coefficients of total particulate matter, ap(λ); phytoplankton, aph(λ); and non-algal particles, ad(λ), as well as the particulate backscattering coefficient, bbp(λ). This analysis is based on an extensive field dataset of concurrent measurements of PON and particulate IOPs in the near-surface oceanic waters and shows that reasonably strong relationships hold across a range of diverse oceanic and coastal marine environments. The coefficients ap(λ) and aph(λ) show the best ability to serve as PON proxies over a broad range of PON from open-ocean oligotrophic to coastal waters. The particulate backscattering coefficient can also provide a good proxy for PON in open-ocean environments. The relationships presented here demonstrate a promising means to assess PON from optical measurements conducted from spaceborne and airborne remote-sensing platforms and in situ autonomous platforms. In support of this potential application, we provide the relationships between PON and spectral IOPs at light wavelengths consistent with those used by satellite ocean color sensors.